Understanding the aggravating factors of falls in the elderly at home (Research, Society and Development, 2022)
Objective: to analyze the characterization and factors associated with falls in the elderly in the home environment in the available scientific literature. Methodology: this is an integrative literature review, outlined by the PICo strategy, conducted in the time frame from 2016 to 2021 in LILACS and PUBMED databases using the following descriptors: elderly, fall accidents, and risk factors. Results: a total of 852 articles were found, then the inclusion and exclusion criteria were applied, making a final total of 08 eligible articles. Discussion: It was identified the prevalence of this injury in elderly women in their homes. It was evidenced that falls are generally governed by two factors: environmental and physiological. Sarcopenia, aligned with hormonal factors, besides the other processes involved in aging, corroborated the worsening of this health problem. Furthermore, it was understood that falls in the elderly can result in serious complications, both physical and mental, leading to prolonged hospitalization, exposure to other pathologies and even the demand for home care. Conclusion: in general, falls have a growing incidence worldwide, being able to go beyond physiological complaints, implying mental health, family configurations, in addition to having a direct impact on autonomy and activities of daily living.